Prognostic significance of mitral regurgitation and tricuspid regurgitation in patients with left ventricular systolic dysfunction - Koelling, Todd M.; Aaronson, Keith D.; Cody, Robert J.; Bach, David S.; Armstrong, William F. (The American heart journal, 2002)
Background Mitral regurgitation (MR) and tricuspid regurgitation (TR) frequently develop in patients with left ventricular systolic dysfunction (LVSD). Ventricular volume overload that occurs in patients with MR and TR may lead to progression of myocardial dysfunction. We hypothesized that MR and TR would provide markers of risk in patients with LVSD. Methods We reviewed clinical, electrocardiographic, and echocardiographic data on 1421 consecutive patients with LVSD (left ventricular ejection fraction ≤35%). Predictors of survival (freedom from death or United Network for Organ Sharing [UNOS]-1 transplantation) were identified in a multivariable analysis with a Cox proportional hazards analysis. The impact of MR and TR (none to mild, moderate, or severe) then was assessed separately with Kaplan-Meier survival analysis. Results During the follow-up period (mean ± SD, 365 ±364 days), death occurred in 435 study subjects (31%) and UNOS-1 transplantation in 28 subjects (2%). Multivariable predictors of poor outcome included increasing MR and TR grade, cancer, coronary artery disease, and absence of an implantable cardiac defibrillator. Relative risk was 1.84 (95% CI 1.43-2.38) for severe MR and 1.55 (95% CI 1.14-2.11) for severe TR. Survival with Kaplan-Meier analysis related inversely to MR grade (none to mild 1004 ±31 days, moderate 795 ±34 days, severe 628 ±47 days, P <.0001) and TR grade (none to mild 977 ±28 days, moderate 737 ±40 days, severe 658 ±55 days, P =.0001). Conclusion Patients with severe MR or TR represent high-risk subsets of patients with LVSD. Future study is warranted to determine whether pharmaceutical or surgical strategies to relieve MR and TR have a favorable impact on survival. (Am Heart J 2002;144:524-9.)